One-Dimensional Zinc Oxide Decorated Cobalt Oxide Nanospheres for Enhanced Gas-Sensing Properties - Zhou, Hang; Xu, Keng; Yang, Yong; Yu, Ting; Yuan, Cailei; Wei, Wenyan; Sun, Yue; Lu, Wenhui (Frontiers in Chemistry, 2018)
In this study, one-dimensional (1D) zinc oxide was loaded on the surface of cobalt oxide microspheres which were assembled by single-crystalline porous nanosheets via a simple heteroepitaxial growth process. This elaborate structure possessed an excellent transducer function from single-crystalline feature of Co3O4 nanosheets and receptor function from zinc oxide nanorods. The structure of the as-prepared hybrid was confirmed via Scanning Electron Microscope (SEM), X-ray diffraction (XRD) and Transmission Electron Microscope (TEM). Gas-sensing tests showed that the gas-sensing properties of the as-designed hybrid were largely improved. The response was about 161 (Ra/Rg) towards 100 ppm ethanol, which is 110 and 10 times higher than that of Co3O4 (Rg/Ra=1.47) and ZnO (Ra/Rg=15), respectively. And the as-designed ZnO/Co3O4 hybrid also shows high selectivity for ethanol. The superior gas-sensing properties were mainly attributed to the as-designed nanostructures that contained super transducer function and super receptor function. The design strategy for gas-sensing materials in this work shed a new light on the exploring of high-performance gas sensors.